Economic Mechanisms to Regulate Environmental Protection Practices in Industrial and Household Waste Management in the Russian Federation - BEZDUDNAYA, ANNA GEROLDOVNA; TREYMAN, MARINA GENNADIEVNA; KSENOFONTOVA, TATYANA YURYEVNA; SMIRNOV, ROMAN VALENTINOVICH; PROKOPENKOV, SERGEY VYACHESLAVOVICH; KOSHELEVA, TATIANA NIKOLAEVNA (The journal of contemporary issues in business and government, 2020)
The study focuses on the aspects of environmental protection practices in the Russian Federation primarily with regard to industrial and household waste management. The paper outlines waste management practices employed in Russia and other countries and provides an efficiency assessment. The basic economic mechanisms, such as tariff regulation, environmental levy and environmental impact fees, are described and assessed in terms of their stimulating effects on waste management improvement in the Russian Federation. Aspects of waste removal under a single regional operator are discussed and a model of public-private partnership in waste management is proposed and detailed.